The impact of tourism on sustainable development in GCC countries - Zmami, Mourad; Ben-Salha, Ousama (Journal of Tourism Management Research, 2024)
GCC nations are putting a premium on the tourism sector to diversify their economies. However, there is a lack of knowledge on the effects of tourism on sustainable development in these countries. This research aims to fill this gap by analyzing the short-run and long-run effects of international tourist arrivals on the three sustainable development pillars, i.e., economic, social, and environmental. GCC nations are putting a premium on the tourism sector to diversify their economies. However, in these countries, there is a lack of knowledge on the effects of tourism on sustainable development. The empirical investigation suggests the existence of significant long-run linkages between tourism and all sustainable development pillars. Moreover, the PMG-ARDL model shows mixed results regarding the impacts of tourism on sustainable development. First, tourism accelerates economic sustainability only in the short-run, while it promotes social sustainability, as represented by job creation, in the long-run. Furthermore, tourism deteriorates the ecological footprint in the short-run. However, it contributes to environmental sustainability in the long-run. Finally, the short-run country-specific analysis corroborates the previous results, suggesting that tourism improves economic sustainability but harms environmental sustainability in all countries. However, the effects of tourism on social sustainability reveal some short-term heterogeneity, as it boosts job creation in Saudi Arabia and Kuwait and reduces it in Oman and the United Arab Emirates. The findings of the present study have significant policy implications for achieving sustainable development goals in GCC. countries.